Precancerous pathways to gastric cancer: a review of experimental animal models recapitulating the correa cascade - Li, Weiqing; Zhang, Tai (Frontiers in Cell and Developmental Biology, 2025)
Gastric cancer remains a significant global health challenge, representing the fifth most commonly diagnosed cancer and the fourth leading cause of cancer-related mortality worldwide. Understanding the pathogenesis of precancerous lesions is crucial for developing effective prevention and treatment strategies. This review provides a comprehensive analysis of animal models for gastric precancerous lesions, categorizing them into Helicobacter infection models, chemical carcinogen or diet-induced models, multifactorial induction models, chemical injury models, and genetically engineered mouse models. We evaluate the advantages and limitations of each model type, with particular focus on their ability to recapitulate the Correa cascade of human gastric carcinogenesis. While Helicobacter felis infection in C57BL/6 mice most closely mirrors the progression from chronic gastritis through metaplasia to dysplasia, these models primarily produce spasmolytic polypeptide-expressing metaplasia rather than true intestinal metaplasia, limiting translational relevance. Chemical carcinogen models reliably produce tumors but often bypass intermediate precancerous stages. Recent advances in genetic engineering, particularly stomach-specific inducible Cre recombinase systems targeting gastric progenitor cells, have yielded models that faithfully reproduce the spectrum of human gastric cancer subtypes with features of metastatic disease. We highlight the importance of standardized histopathological evaluation methodologies and discuss future research directions, including integration of advanced technologies such as single-cell RNA sequencing with existing animal models, development of organoid models, and investigation of interactions among genetic predisposition, Helicobacter infection, and environmental factors. This review provides a valuable reference for researchers investigating gastric precancerous lesions and offers insights for the development of more effective prevention and treatment strategies.